Ceric oxide / UiO-66 (Ce / Ti) composite photocatalyst as well as preparation method and application thereof
The ceria/UiO-66 (Ce/Ti) composite photocatalyst was prepared by the solvothermal method, which solved the problems of low mineralization rate and unstable material when the existing photocatalyst degrades tetracycline in water, and achieved efficient tetracycline degradation and structural stability of the catalyst.
Patent Information
- Application Number
- CN202411955378.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-14
AI Technical Summary
When existing photocatalysts degrade tetracycline in water, the mineralization rate is low, the intermediate poison is produced, and the material properties and structure are unstable, making it difficult to effectively utilize visible light.
The ceria/UiO-66 (Ce/Ti) composite photocatalyst was prepared by solvothermal method, and a heterostructure was formed to improve the photocatalytic performance by combining the catalytic activity of ceria and the structural stability of UiO-66 (Ce/Ti).
The efficient degradation of tetracycline under visible light was achieved, and the mineralization rate reached 63%, avoiding the production of intermediate poisons, and significantly improving the structural stability and photocatalytic activity of the catalyst.
Smart Images

Figure CN119608244A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic degradation of water pollution, and in particular relates to a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst and a preparation method and application thereof. Background Art
[0002] With the increase of industrial sewage and dye wastewater, the abuse of pesticides, and the use of medical supplies, a large number of emerging organic pollutants are being generated, causing serious water pollution, and tetracycline is one of the most commonly used antibiotics. According to statistics, the excretion rate of all tetracycline analogs exceeds 70%, and they enter the aquatic environment in a changed or unchanged form, affecting aquatic microorganisms and macroorganisms. Therefore, it is urgent to find a way to deal with tetracycline pollution in water.
[0003] Ceria has been widely used in the preparation of photocatalysts due to its excellent structural stability, good redox ability, environmental friendliness and abundant oxygen vacancies. It has potential application prospects in the degradation of organic pollutants and photocatalytic water decomposition. However, the band gap of CeO2 is large (about 3.1 eV), which limits its utilization efficiency of visible light. In addition, the high electron-hole recombination rate will also weaken its photocatalytic performance. In order to improve the visible light catalytic performance of ceria and overcome the recombination of photogenerated carriers, scholars have modified ceria by various means, such as ion doping, precious metal loading, etc. to improve its photocatalytic performance, but poor stability and high synthesis cost limit its practical application.
[0004] UiO-66(Ce), as a member of the metal organic framework (MOF) family, has a unique low-energy 4f electron layer structure and the reversible redox properties of cerium ions (i.e., Ce 3+ With Ce 4+ However, in practical applications, this material faces two major challenges: first, the ligand-to-metal charge transfer (LMCT) process and the generation of reduced photogenerated electrons are limited by Ce. 3+ / Ce 4+ The binding strength between the orbital and the organic ligand is insufficient; secondly, the structural stability of UiO-66 (Ce) needs to be improved, which to some extent hinders its widespread application. The existing technology combines cerium dioxide and UiO-66 (Ce) to solve the above problems, but the composite material of cerium dioxide and UiO-66 (Ce) has problems such as low mineralization rate, generation of intermediate poisons, and unstable catalyst material performance and structure when degrading tetracycline in wastewater. Summary of the invention
[0005] In view of the background technical problems, the present invention provides a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst and a preparation method and application thereof by a solvothermal method. The purpose of the present invention is to overcome the defects of traditional photocatalysts such as poor photocatalytic activity, short service life, difficulty in degrading antibiotics in wastewater, and low mineralization rate, and to compound the cerium dioxide catalyst in the metal organic framework UiO-66 (Ce / Ti) to obtain a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst, and to prove that the above-mentioned cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst can effectively degrade tetracycline in wastewater under visible light.
[0006] To achieve the above object, the technical solution adopted by the present invention is: the preparation method of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst comprises the following steps:
[0007] (1) dissolving cerium nitrate hexahydrate in a mixed solution of water and ethanol, adding acetic acid, stirring at room temperature, then adding polyvinyl pyrrolidone and heating, centrifuging, washing, drying, and finally calcining to obtain cerium dioxide;
[0008] (2) weighing phthalic acid and dissolving it in DMF, stirring, adding ammonium nitrate cerium aqueous solution and heating, centrifuging, washing, and drying in sequence, and finally obtaining UiO-66(Ce);
[0009] (3) dissolving the cerium dioxide obtained in step (1) in DMF, adding titanocene dichloride and UiO-66 (Ce) obtained in step (2), heating, centrifuging, washing and drying in sequence to obtain a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst.
[0010] As an embodiment of the present invention, in step (1), the volume ratio of water, ethanol and acetic acid is 1:2:0.1, and the stirring time is 1 to 2 hours.
[0011] As an embodiment of the present invention, in the step (1), the mass of polyvinyl pyrrolidone is 60-80% of the cerium nitrate hexahydrate, the heating temperature is 180° C., and the heating time is 22-24 hours.
[0012] As an embodiment of the present invention, in the step (1), the calcination temperature is 500-600°C, the calcination time is 2h, and the heating rate is 1-5°C / min.
[0013] As an embodiment of the present invention, in the step (2), the molar ratio of terephthalic acid to ammonium cerium nitrate is 1:1, the concentration of the aqueous solution of ammonium cerium nitrate is 0.533 mol / L, the volume is 2.4 ml, the heating temperature is 100-120° C., and the time is 30-60 min.
[0014] As an embodiment of the present invention, the molar ratio of cerium dioxide, dichlorotantalum, and UiO-66(Ce) added in step (3) is (0.075-0.375):1:1.
[0015] As an embodiment of the present invention, the heating temperature in step (3) is 100° C. and the heating time is 3-4 hours.
[0016] The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst prepared by the preparation method of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst of the present invention.
[0017] The invention discloses an application of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst in photocatalytic degradation of antibiotics in wastewater.
[0018] Compared with the prior art, the advantages of the present invention are:
[0019] (1) The present invention prepares a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst by a solvothermal method, and the synthesis operation is simple, the raw materials are cheap, and the synthesis process is green and environmentally friendly. The material prepared by the present invention has extremely high porosity and specific surface area, which is conducive to adsorption, and has a longer excited state and easier charge-hole separation, creating favorable conditions for photocatalytic reaction.
[0020] (2) The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst prepared by the present invention can achieve a good mineralization rate (63%) for tetracycline and avoid the production of toxic intermediates; in addition, it exhibits good structural stability in multiple photocatalytic removal of tetracycline cycle experiments.
[0021] (3) The present invention is the first to combine cerium dioxide and UiO-66 (Ce / Ti) to form a heterostructure, which effectively solves the problem of insufficient response of cerium dioxide in the visible light region and significantly reduces the recombination rate of photogenerated carriers in UiO-66 (Ce / Ti), thereby achieving mutual improvement and synergistic optimization of the performance of the two, and has broad application value and prospects in the field of environmental governance.
[0022] (4) The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst of the present invention treats tetracycline wastewater under visible light, and the removal rate of tetracycline is as high as 93.7% within 120 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1X-ray diffraction patterns of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, the cerium dioxide catalyst prepared in Comparative Example 1, and the UiO-66 (Ce / Ti) catalyst (U(Ce / Ti)) prepared in Comparative Example 2.
[0024] Figure 2 SEM images of the materials prepared in Example 1 and Comparative Examples 1-2; (a) is a scanning electron microscope image of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1; (b) is a scanning electron microscope image of the cerium dioxide catalyst prepared in Comparative Example 1; (c) is a scanning electron microscope image of the UiO-66 (Ce / Ti) catalyst prepared in Comparative Example 2.
[0025] Figure 3 These are transmission electron micrographs of different resolutions of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst (UC20) prepared in Example 1 of the present invention, (a) is a low-magnification TEM, (b) is a high-magnification TEM, and (c) is a HRTEM.
[0026] Figure 4 Fourier transform infrared spectra of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, the cerium dioxide catalyst prepared in Comparative Example 1, and the UiO-66 (Ce / Ti) catalyst prepared in Comparative Example 2.
[0027] Figure 5 X-ray photoelectron energy spectra of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention and the cerium dioxide catalyst prepared in Comparative Example 1.
[0028] Figure 6 These are the ultraviolet-visible diffuse reflectance images of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, the cerium dioxide prepared in Comparative Example 1, and the UiO-66 (Ce / Ti) catalyst prepared in Comparative Example 2.
[0029] Figure 7 This is a diagram showing the removal effect of tetracycline under visible light by the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalysts (UC5, UC10, UC15, UC20, UC30) prepared in Example 1 of the present invention and the materials prepared in Comparative Examples 1-3. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0031] Example 1
[0032] A method for preparing a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst comprises the following steps:
[0033] (1) Weigh 1 g of cerium nitrate hexahydrate and disperse it in a mixed solution of 10 mL of deionized water and 20 mL of ethanol. Add 1 mL of acetic acid and stir at room temperature of 20-30°C. Add 0.8 g of polyvinyl pyrrolidone and continue stirring at 600 rpm for 30 min. Heat at 180°C for 22 h, centrifuge and precipitate. Wash with ethanol and deionized water, and dry at 60°C to obtain gray powdered cerium dioxide. Transfer the powder into a muffle furnace, increase the temperature at a rate of 1-5°C / min, and calcine at 500-600°C in air for 2 hours to obtain yellow powdered cerium dioxide.
[0034] (2) 1.3 mmol of terephthalic acid was dissolved in 22.5 mL of N,N-dimethylformamide. After sufficient stirring, 0.533 mol / L of cerium ammonium nitrate aqueous solution was added and stirring was continued to form a light yellow suspension. The suspension was heated at 100°C for 30 min, centrifuged and precipitated. The suspension was washed with N,N-dimethylformamide and ethanol and dried at 80°C to obtain powder UiO-66(Ce).
[0035] (3) 20 mg of cerium dioxide was fully dissolved in 25 mL of N,N-dimethylformamide, and after being fully stirred at 800 rpm, 97.5 mg of dichlorotantalum and 130 mg of UiO-66 (Ce) were added, and the mixture was heated at 100 °C for 3 h. The mixture was centrifuged and precipitated. The mixture was washed with N,N-dimethylformamide and ethanol, and dried at 80 °C to obtain a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst (UC20).
[0036] In this embodiment, a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst with different amounts of cerium dioxide added was also prepared. Step (1) was the same as step (2), except that the amount of cerium dioxide added in step (3) was 5 mg, 10 mg, 15 mg, and 30 mg, respectively, to obtain composite UC5, composite UC10, composite UC15, and composite UC30, and the corresponding composite photocatalysts obtained were UC5, UC10, UC15, UC20, and UC30.
[0037] The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared according to Example 1 of the present invention was subjected to transmission electron microscopy analysis. Figure 3 It is shown that UiO-66(Ce / Ti) and ceria form a close interface, and the lattice spacing of 0.312 nm is attributed to the (111) plane of CeO2, further proving the successful synthesis of the composite photocatalyst.
[0038] Comparative Example 1
[0039] A preparation method of a cerium dioxide catalyst comprises the following steps:
[0040] Weigh 1 g of cerium nitrate hexahydrate and disperse it in a mixed solution of 10 mL of deionized water and 20 mL of ethanol. Add 1 mL of acetic acid and stir at room temperature of 20-30 ° C. Add 0.8 g of polyvinyl pyrrolidone and continue stirring at 600 rpm for 30 min. Heat at 180 ° C for 22 h, centrifuge and precipitate. Wash with ethanol and deionized water, and dry at 60 ° C to obtain gray powder cerium dioxide. Move the powder into a muffle furnace with a heating rate of 1-5 ° C / min. Calcinate at 500-600 ° C in air for 2 hours to obtain yellow powder cerium dioxide.
[0041] According to the X-ray photoelectron spectrum of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, Figure 5 The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 is composed of C, O, Ce, and Ti elements; the ultraviolet visible diffuse reflectance image of the cerium dioxide catalyst prepared in Comparative Example 1, Figure 6 The results show that the absorption edge of ceria is observed at 383nm, and UiO-66 (Ce / Ti) exhibits an absorption edge at 396nm. Compared with ceria and UiO-66 (Ce / Ti), the absorption edge of UC20 shows a slight red shift, and the light absorption capacity of the surface composite material UC20 is enhanced, which is beneficial to improve the photocatalytic activity.
[0042] Comparative Example 2
[0043] A preparation method of a UiO-66 (Ce / Ti) photocatalyst comprises the following steps:
[0044] (1) 1.3 mmol of terephthalic acid was dissolved in 22.5 mL of N,N-dimethylformamide. After sufficient stirring, 0.533 mol / L of cerium ammonium nitrate aqueous solution was added and stirring was continued to form a light yellow suspension. The suspension was heated at 100°C for 30 min, centrifuged and precipitated. The suspension was washed with N,N-dimethylformamide and ethanol and dried at 80°C to obtain powdered UiO-66(Ce).
[0045] (2) 97.5 mg of dichlorotitanium and 130 mg of UiO-66(Ce) were fully dissolved in 25 mL of N,N-dimethylformamide, stirred at 800 rpm, heated at 100°C for 3 h, centrifuged, washed with N,N-dimethylformamide and ethanol, and dried at 80°C to obtain UiO-66(Ce / Ti) photocatalyst, recorded as UiO-66(Ce / Ti).
[0046] The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, the cerium dioxide prepared in Comparative Example 1 and the UiO-66 (Ce / Ti) catalyst prepared in Comparative Example 2 were subjected to scanning electron microscopy (SEM) and Fourier infrared spectroscopy (IR) respectively: According to the SEM results, Figure 2 The cubic structure of ceria shown in (a) is consistent with XRD diffraction; Figure 2 (b) shows that UiO-66(Ce / Ti) has polyhedral shapes of different sizes. Figure 2 (c) After the composite material is formed, cerium dioxide is tightly wrapped by UiO-66 (Ce / Ti); from the IR results, it can be seen that Figure 4 The characteristic absorption peak at 440 cm-1 corresponds to the Ce-O-Ce bond of cerium dioxide; the peaks at 1505 cm-1 and 1651 cm-1 are attributed to the CH bending vibration of the organic ligand terephthalic acid in UiO-66 (Ce / Ti); the peak at 671 cm-1 can be attributed to the Ti-O bond in the UiO-66 (Ce / Ti) structure, confirming the successful preparation of the composite material.
[0047] XRD analysis was performed on the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst UC20 prepared in Example 1 of the present invention, the cerium dioxide prepared in Comparative Example 1, and the UiO-66 (Ce / Ti) prepared in Comparative Example 2. Figure 1 It can be seen that the ceria / UiO-66 (Ce / Ti) composite photocatalyst UC20 shows clear diffraction peaks with ceria and UiO-66 (Ce / Ti); all diffraction peaks of ceria correspond to its standard card
[0048] (PDF#78-00694); The XRD spectrum of UiO-66 (Ce / Ti) has three prominent diffraction peaks at 2θ=7.07°(111), 8.17°(002) and 11.59°(022), which matches the MOF structure; preliminary verification shows that the preparation of cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst (UC20) has been successfully synthesized.
[0049] Comparative Example 3
[0050] A preparation method of a cerium dioxide / UiO-66 (Ce) photocatalyst comprises the following steps:
[0051] (1) Weigh 1 g of cerium nitrate hexahydrate and disperse it in a mixed solution of 10 mL of deionized water and 20 mL of ethanol. Add 1 mL of acetic acid and stir at room temperature of 20-30°C. Add 0.8 g of polyvinyl pyrrolidone and continue stirring at 600 rpm for 30 min. Heat at 180°C for 22 h, centrifuge and precipitate. Wash with ethanol and deionized water, and dry at 60°C to obtain gray powdered cerium dioxide. Transfer the powder into a muffle furnace, increase the temperature at a rate of 1-5°C / min, and calcine at 500-600°C in air for 2 hours to obtain yellow powdered cerium dioxide.
[0052] (2) 1.3 mmol of terephthalic acid was dissolved in 22.5 mL of N,N-dimethylformamide. After sufficient stirring, 0.533 mol / L of cerium ammonium nitrate aqueous solution was added and stirring was continued to form a light yellow suspension. The suspension was heated at 100°C for 30 min, centrifuged and precipitated. The suspension was washed with N,N-dimethylformamide and ethanol and dried at 80°C to obtain powder UiO-66(Ce).
[0053] (3) 20 mg of cerium dioxide was fully dissolved in 25 mL of N,N-dimethylformamide, and after being fully stirred at 800 rpm, 130 mg of UiO-66 (Ce) was added, and the mixture was heated at 100 °C for 3 h. The mixture was centrifuged and precipitated. The mixture was washed with N,N-dimethylformamide and ethanol, and dried at 80 °C to obtain a cerium dioxide / UiO-66 (Ce) composite photocatalyst.
[0054] Effect Example 1
[0055] The application of the photocatalyst prepared in Example 1 and Comparative Examples 1-3 in degrading tetracycline in wastewater comprises the following steps:
[0056] Weigh 10 mg of each of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst (UC5, UC10, UC20, UC15, UC30) prepared in Example 1, the cerium dioxide catalyst prepared in Comparative Example 1, the UiO-66 (Ce / Ti) catalyst prepared in Comparative Example 2, and the cerium dioxide / UiO-66 (Ce) composite photocatalyst prepared in Comparative Example 3, and add them to 50 mL of a tetracycline solution with an initial concentration of 30 mg / L, respectively, and stir at 300 r / min in the dark for 30 min to reach adsorption equilibrium. Irradiate with a 300w xenon lamp equipped with a 420nm cutoff filter for 120 min, take 3.5 mL of the solution every 30 min, and measure the absorbance at 357 nm to calculate the degradation rate.
[0057] The removal effects of four composite photocatalysts on tetracycline in wastewater under visible light were investigated: Figure 7It can be seen that under visible light, the removal rates of tetracycline by the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalysts UC5, UC10, UC15, UC20, and UC30 prepared in Example 1 within 120 minutes were 86.87%, 85.49%, 82.54%, 93.78%, and 68.68%, respectively. The removal rates of tetracycline by the cerium dioxide prepared in Comparative Example 1, the UiO-66 (Ce / Ti) prepared in Comparative Example 2, and the cerium dioxide / UiO-66 (Ce) prepared in Comparative Example 3 were 17%, 66.12%, and 31.3%, respectively. The composite material prepared in Comparative Example 3 cannot form a heterogeneous structure, resulting in a significant decrease in photocatalytic activity and a relatively significant decrease in photocatalytic stability.
[0058] The mineralization rate of tetracycline by UC20 prepared in Example 1 reached 63% within 120 minutes. Due to the poor activity of the catalyst, the degradation of tetracycline was not complete. The mineralization rates of tetracycline by cerium dioxide prepared in Comparative Example 1, UiO-66 (Ce / Ti) prepared in Comparative Example 2, and cerium dioxide / UiO-66 (Ce) prepared in Comparative Example 3 were relatively low within 120 minutes.
[0059] After 5 cycles of experiments, the photocatalytic degradation retention rates of tetracycline by UC20 prepared in Example 1, cerium dioxide prepared in Comparative Example 1, UiO-66 (Ce / Ti) prepared in Comparative Example 2, and cerium dioxide / UiO-66 (Ce) prepared in Comparative Example 3 were 90.9%, 88.2%, 85.1%, and 80.8%, respectively. Therefore, the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst prepared by the present invention has good structural stability.
Claims
1. A method for preparing a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst, characterized in that: The steps include: (1) dissolving cerium nitrate hexahydrate in a mixed solution of water and ethanol, adding acetic acid and stirring at room temperature, then adding polyvinyl pyrrolidone and heating, centrifuging, washing, drying, and finally calcining to obtain cerium dioxide; (2) weighing terephthalic acid, dissolving it in DMF and stirring, adding ammonium cerium nitrate aqueous solution and heating, centrifuging, washing and drying in sequence to obtain UiO-66(Ce); (3) dissolving the cerium dioxide obtained in step (1) in DMF, adding titanocene dichloride and UiO-66 (Ce) obtained in step (2), heating, centrifuging, washing and drying in sequence to obtain a cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst.
2. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: In the step (1), the volume ratio of water, ethanol and acetic acid is 1:2:0.
1.
3. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: In the step (1), the mass of polyvinyl pyrrolidone is 60-80% of the cerium nitrate hexahydrate, the heating temperature is 160° C.-180° C., and the heating time is 22-24 hours.
4. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: In the step (1), the calcination temperature is 500-600° C., the calcination time is 1-2 hours, and the heating rate is 1-5° C. / min.
5. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: In the step (2), the molar ratio of terephthalic acid to ammonium cerium nitrate is 1:1, the heating temperature is 100-120° C., and the heating time is 30-60 min.
6. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: In the step (3), the molar ratio of cerium dioxide, dichlorotantalum and UiO-66(Ce) is (0.075-0.375):1:
1.
7. The method for preparing the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 1, characterized in that: The heating temperature in step (3) is 100-120° C. and the heating time is 3-4 hours.
8. The cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst prepared according to the preparation method of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to any one of claims 1 to 7.
9. Use of the cerium dioxide / UiO-66 (Ce / Ti) composite photocatalyst according to claim 8 in photocatalytic degradation of antibiotics in wastewater.
Citation Information
Patent Citations
Flaky CeO2 / UIO-66-NH2 composite photocatalytic material and preparation method thereof
CN113318792A